2015
DOI: 10.1002/jsfa.7228
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous strategy enhancing the sensitivity of the fluorescence polarization immunoassay of clinafloxacin in goat milk

Abstract: This proposed heterologous strategy for enhanced FPIA is sensitive and rapid enough for the high-throughput detection of clinafloxacin residue in goat milk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Another assay has been established a homogenous FPIA based on the monoclonal antibody and the tracer for the simultaneous determination of cefalexin and cefadroxil in milk samples (Zhang, Wang, Mi, Wenren, & Wen, 2014). A heterologous structure of FPIA was established for the determination of clinafloxacin in goat milk which has been observed to be more sensitive than homologous structure (Chen, Shanin, et al, 2016). Another sensitive quantitative FPIA immunochemical approach has been reported for the screening of gentamicin in milk samples.…”
Section: Fluorescence Immunoassay/fluorescence Polarization Immunoassaymentioning
confidence: 99%
“…Another assay has been established a homogenous FPIA based on the monoclonal antibody and the tracer for the simultaneous determination of cefalexin and cefadroxil in milk samples (Zhang, Wang, Mi, Wenren, & Wen, 2014). A heterologous structure of FPIA was established for the determination of clinafloxacin in goat milk which has been observed to be more sensitive than homologous structure (Chen, Shanin, et al, 2016). Another sensitive quantitative FPIA immunochemical approach has been reported for the screening of gentamicin in milk samples.…”
Section: Fluorescence Immunoassay/fluorescence Polarization Immunoassaymentioning
confidence: 99%
“…With the heterologous tracer 5-OH-DCF-AMF, approximately the same sensitivity as with the homologous tracer DCF-Ahx-AMF was obtained (compare Table 2). According to some studies [27][28][29], heterologous tracers may improve the sensitivity.…”
Section: Sensitivity and Measurement Rangementioning
confidence: 99%
“…Some studies have been reported for the detection of FQs by FPIA [19][20][21]. In our previous study, heterologous tracers were recruited to establish FPIA for the detection of six FQs based on anti-clinfloxacin polyclonal antibody (pAb) [22]. However, since enrofloxacin is more popular than other FQs [15], specific immunoassays are needed to accurately quantify enrofloxacin residues.…”
Section: Introductionmentioning
confidence: 99%